Speciation reversal in European whitefish (Coregonus lavaretus (L.)) caused by competitor invasion - Bhat, Shripathi; Amundsen, Per-Arne; Knudsen, Rune; Gjelland, Karl Øystein; Fevolden, Svein-Erik; Bernatchez, Louis; Præbel, Kim (PLoS ONE, 2014)
Invasion of exotic species has caused the loss of biodiversity and imparts evolutionary and ecological changes in the introduced systems. In northern Fennoscandia, European whitefish (Coregonus lavaretus (L.)) is a highly polymorphic species displaying adaptive radiations into partially reproductively isolated and thus genetically differentiated sympatric morphs utilizing the planktivorous and benthivorous food niche in many lakes. In 1993, Lake Skrukkebukta was invaded by vendace (Coregonus albula (L.)) which is a zooplanktivorous specialist. The vendace displaced the densely rakered whitefish from its preferred pelagic niche to the benthic habitat harbouring the large sparsely rakered whitefish. In this study, we investigate the potential influence of the vendace invasion on the breakdown of reproductive isolation between the two whitefish morphs. We inferred the genotypic and phenotypic differentiation between the two morphs collected at the arrival (1993) and 15 years after (2008) the vendace invasion using 16 microsatellite loci and gill raker numbers, the most distinctive adaptive phenotypic trait between them. The comparison of gill raker number distributions revealed two modes growing closer over 15 years following the invasion. Bayesian analyses of genotypes revealed that the two genetically distinct whitefish morphs that existed in 1993 had collapsed into a single population in 2008. The decline in association between the gill raker numbers and admixture values over 15 years corroborates the findings from the Bayesian analysis. Our study thus suggests an apparent decrease of reproductive isolation in a morph-pair of European whitefish within 15 years (. 3 generations) following the invasion of a superior trophic competitor (vendace) in a subarctic lake, reflecting a situation of ‘‘speciation in reverse’’.